2018
DOI: 10.1111/jace.16030
|View full text |Cite
|
Sign up to set email alerts
|

Effect of heating rate on properties of transparent aluminum oxynitride sintered by spark plasma sintering

Abstract: High heating rates ranging from 50 to 250°C/min are selected to rapidly sinter transparent aluminum oxynitride (AlON) ceramics by spark plasma sintering (SPS) at 1600°C under 60 MPa using a bimodal AlON powder synthesized by the carbothermal reduction and nitridation method. With 1 minute holding time before cooling, all the specimens show high density and high transparence. The maximum transmittance is up to 74.5%-80.6%, where the maximum transmittance is positively correlated with the heating rate. Further a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 37 publications
2
3
0
Order By: Relevance
“…In Figure 3, the emergence of the diffraction patterns of the Al 2 O 3 phase gives a hint of the decomposition of AlON at 1200°C, which means that the nitrogen‐rich AlON powder we synthesized is not very stable during the sintering. This phenomenon is also be found by other researchers 15,16 . When the temperature is increased to 1400°C, the diffraction patterns of AlN phase also become notable, which again suggests that parts of AlON have decomposed.…”
Section: Resultssupporting
confidence: 84%
See 3 more Smart Citations
“…In Figure 3, the emergence of the diffraction patterns of the Al 2 O 3 phase gives a hint of the decomposition of AlON at 1200°C, which means that the nitrogen‐rich AlON powder we synthesized is not very stable during the sintering. This phenomenon is also be found by other researchers 15,16 . When the temperature is increased to 1400°C, the diffraction patterns of AlN phase also become notable, which again suggests that parts of AlON have decomposed.…”
Section: Resultssupporting
confidence: 84%
“…This phenomenon is also be found by other researchers. 15,16 When the temperature is increased to 1400 • C, the diffraction patterns of AlN phase also become notable, which again suggests that parts of AlON According to the AlON phase diagrams of Willems, 17 McCauley and Corbin, 18,19 and McCauley et al, 20 AlON is not stable under 1600 • C, so the decomposition of AlON was found in this work. With the increase of temperature, the solid solution range of AlN-Al 2 O 3 becomes wider, so we found the re-formation of AlON.…”
Section: Resultssupporting
confidence: 56%
See 2 more Smart Citations
“…They found that AlON transparent ceramics with high transmittance can be sintered without pressure at 1880 ℃. Shan et al [7] from Dalian Maritime University used SPS to study the heating rate and its effects on the physical characteristics of the transparent ceramic AlON. They found that increasing the heating rate from 50 ℃/min to 250 ℃/min can increase the visible transmittance to 74.6% -80.6%.…”
Section: Introductionmentioning
confidence: 99%